Mapeamento estratégico empresarial através do modelo de Balanced Scorecard de sustentabilidade na indústria Lactobom - Barszcz, Sérgio Henrique (2007)
The aim of this study is to prove that Strategic Maps show the need to use the Balanced Scorecard of Sustainability model in companies that are committed with social and environmental actions aiming at the sustainable development, however, have no suitable strategic instruction for the managerial sustainability. A study case in the Milk Industry Company Lactobom was carried out. This company has developed such actions, but is not strategically instructed. The research tools used were observation and semi-structured interview, both developed and applied based on the architecture of Balanced Scorecard of Sustainability. Through data collection, it was possible to identify the strategic aims of the company, which resulted in the Lactobom Strategic Map. This was later presented to the company, which recognized the need for the model applied by the research to their management.